2019
DOI: 10.1016/j.gaitpost.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative description of self-selected walking in adults with Achondroplasia using the gait profile score

Abstract: Background: Achondroplasia is characterised by a shorter appendicular limb-to-torso ratio, compared to age matched individuals of average stature (controls). Previous work shows gait kinematics of individuals with Achondroplasia differing to controls, but no global quantification of gait has been made in adults with Achondroplasia. Aim: The aim of this study was to quantify gait differences between a group of adult males with Achondroplasia and controls during self-selected walking (SSW) using the Gait Profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
4
16
0
4
Order By: Relevance
“…1 and 2). These data not only confirm the previous sagittal descriptions of groups with Achondroplasia [4,[11][12][13], but also helps explain the larger GPS reported in this population [4]. It has previously been suggested that the gait of individuals with Achondroplasia is more flexed to accommodate toeclearance during swing phase [11].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…1 and 2). These data not only confirm the previous sagittal descriptions of groups with Achondroplasia [4,[11][12][13], but also helps explain the larger GPS reported in this population [4]. It has previously been suggested that the gait of individuals with Achondroplasia is more flexed to accommodate toeclearance during swing phase [11].…”
Section: Discussionsupporting
confidence: 89%
“…The slower SSW of the Achondroplasic group compared to controls was unsurprising given gait speed is determined by stride length, which is in turn determined somewhat by leg length which is short in the Achondroplasic group [4,16]. Despite the difference in SSW speed between groups, no time normalised temporal differences existed, which is consistent with other spatio-temporal observations of gait in shorter versus taller comparisons [18].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations